Hesperidoside abolishes dichlorvos-mediated neurotoxicity in rats by suppressing oxidative stress, acetylcholinesterase inhibition, and NF-κB-p65/p53/caspase-3-mediated apoptosis - Adio J. Akamo; Adetutu O. Ojelabi; Oluwatobi T. Somade; Iyabode A. Kehinde; Adewale M. Taiwo; Boluwatife A. Olagunju; Mushafau A. Akinsanya; Adedayo A. Adebisi; Tobi S. Adekunbi; Abiola F. Adenowo; Florence Anifowose; Olufemi M. Ajagun-Ogunleye; et al. (Phytomedicine Plus)
Background: In third-world countries, poisoning due to dichlorvos (DDVP), an organophosphate insecticide, is prevalent due to its widespread usage in household and agriculture, with the brain bearing the brunt of the consequences. Hence, this study assessed the likely beneficial impact of hesperidoside (HESP) on the DDVP-mediated cerebral dysfunction in rat model. Method: Randomization was employed to earmark forty-two rats into seven groups: control, DDVP alone (8 mg.kg⁻¹day⁻¹), DDVP plus HESP (50 and 100 mg.kg⁻¹day⁻¹) and reference drug atropine (0.2 mg.kg⁻¹day⁻¹), and HESP alone (50 and 100 mg.kg⁻¹day⁻¹). Results: HESP intervention remarkably (p < 0.05) mitigated DDVP-potentiated augmentations in cerebral concentrations of H₂O₂, NO, and malondialdehyde; impaired DDVP-induced decrease in cerebral GSH, GST, SOD, catalase, glutathione peroxidase, and acetylcholinesterase; significantly (p < 0.05) suppressed DDVP-invoked upregulation of mRNA expression of NF-κB-p65, p53, BAX, caspase-3, and TNF-α; and significantly (p < 0.05) revoked DDVP-incited downregulation of interleukin-10. Conclusion: HESP chemotherapeutic interventions enhanced cerebral functions in DDVP-treated rats by abrogating oxidative stress, acetylcholinesterase inhibition, and NF-κB-p65/p53/caspases-3 signaling.